Detective Dinosaur - Skofield, James; Alley, R. W. (Robert W.) (New York : HarperCollins Publishers, 1996)
Detective Dinosaur and Officer Pterodactyl are challenged to solve three cases when a hat is missing, a shoe squeaks, and a loud clanging comes from a dark alley at night.